Social Media and Legal Accountability: The Role Of Public Opinion In Judicial Processes - Layla Abbas; Rami Mansour (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This article investigates the impact of social media on judicial processes, focusing on how public opinion influences legal accountability. Through case studies and analyses of high-profile cases, the research examines the power dynamics between public opinion and legal frameworks, including the risks and benefits of digital activism. Findings suggest that while social media can support transparency and public engagement, it may also lead to biased perceptions that challenge judicial impartiality. The study highlights the need for a balanced approach to harness the benefits of social media in fostering accountability without compromising the integrity of the judicial process.